Development of a non-test instrument to measure lecturers’ understanding of the STEM approach and its implementation in islamic studies courses - Louisiana Muliawati; Hartoyo, Zainal; Della Amrina Yusra; Haerul Pathoni (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2025)
Purpose – This study aims to develop a non-test instrument to measure lecturers’ understanding and perceptions of the STEM (Science, Technology, Engineering, and Mathematics) approach and its implementation in Islamic studies courses at State Islamic Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Negeri/ PTKIN). Design/methods/approach – This study employed a Research and Development (R&D) method, specifically using a development and validation approach. The instrument development process involved expert validation, reliability testing, and field trials. Findings – The study produced a non-test instrument designed to measure lecturers’ perceptions and understanding of the STEM approach and its application in Islamic studies courses at PTKIN. The instrument successfully passed expert validation stages, including content and face validity. It achieved a very high validity level of 97% in accordance with the standards set by the National Education Standards Board (BSNP). Reliability testing using Cronbach’s Alpha indicated acceptable internal consistency, although categorized as low, with coefficients of 0.639 for the material aspect, 0.598 for constructiveness, and 0.569 for the language aspect. These results indicate that the instrument is suitable for use. Field trial results revealed that the majority of lecturers were familiar with the STEM approach (65% or 15 lecturers) and understood its urgency in integrating interdisciplinary knowledge into Islamic studies courses (56% or 13 lecturers). Research implications/limitations – The developed instrument is a valid and reliable tool for assessing lecturers’ understanding and perceptions of the STEM approach. The findings indicate the need for further training, increased resources, and improved infrastructure to support the effective integration of STEM into Islamic studies courses at PTKIN. Originality/value – Research on the development of non-test instruments related to STEM is still very limited in PTKIN contexts. This study provides an initial contribution, with future research directed toward developing STEM–Islamic learning tools.